Grow-out of transfection and non transfection black tiger shrimp broodstock, Penaeus monodon in concrete pond. Issue 1 (October 2020) - Suwoyo, H S; Sahabuddin,; Sahrijanna, A; Septiningsih, E; Mulyaningrum, S R H
Abstract: Broodstock supply is part of the overall sustainability of tiger shrimp hatchery production. The purpose of this study aimed to evaluate the growth performance and survival rate of broodstock of tiger shrimp transfection and non transfection. This research was conducted at 1000 m 2 size of two ponds in Experimental Pond Installation, Research Institute for Coastal Aquaculture, in Punaga Village, Takalar Regency, South Sulawesi. The treatment was different kinds of broodstocks, which were: broodstock candidates of tiger shrimp transfection (A) and non transfection, (B). The 67.9 to 78.9 g/ind of broodstock candidates were stocked 0.2 ind.m −2 and then reared for 90 days. During rearing period, these shrimp were fed using enrichment commercial pelleted feed with content 36-38% of protein in dosage of 10-4%/body weight. Entering the last month of rearing period is given fresh feed were seaworms and squid (3% biomass weight). Feeding frequency was applied in the morning and in the evening. Measured variables were growth, daily growth rate, survival rate and water quality The results showed that the average final weight of transfection and non-transfection black tiger shrimp broodstocks was 80.29 and 92.57 g/ind, respectively. Survival rate of tiger shrimp in this study ranged from 71.5 to 81.5%. The range of water quality during the study still supported the growth and survival rate of black tiger shrimp.